A Case of Thyroglossal Duct Cyst in a 13-Year-Old Female Patient on Her First Visit to the Hospital - Rahman, Aulia; Mufrizal, Mufrizal (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Thyroglossal duct cyst is the most common congenital neck abnormality, resulting from failure of the thyroglossal duct to obliterate during the embryogenesis of the thyroid gland. A 13-year-old female patient complaining of a lump under her chin for approximately 5 years prior to admission. Initially, the lump was painless, but two weeks before admission, it enlarged and was accompanied by throbbing pain and signs of local inflammation. Physical examination revealed a mass in the submental region with tenderness and erythema, without cervical lymph node enlargement. FNAB Examination result showed a thyroglossal duct cyst without signs of malignancy. Based on the anamnesis, physical examination, and supporting examination results, the patient was diagnosed with a thyroglossal duct cyst. The patient underwent a Sistrunk procedure under general anesthesia. The operation approximately 40 minutes and involved excision of the cyst and duct tract, resection of the middle part of hyoid bone, and placement of a handscoon drain. Postoperative wound care proceeded well, improvement in pain, stable condition, and no complications of bleeding or surgical wound infection. On the fourth postoperative day, the patient's condition was stable and she was allowed to go home with oral therapy.